Two metabolic enzymes, LDH and FASN, serum levels in Bladder cancer patients - Fattahi, Mohammad Javad; Sedaghat, Fatemeh; Haghshenas, Mohammad Reza; Ariafar, Ali; Shiravani, Zahra; Malekzadeh, Mahyar; Madani, Shima (Caspian journal of internal medicine, 2024)
Bladder cancer is one of the most common cancers in the world and is associated with high treatment costs and mortality. The role of different enzymes and molecules in this cancer has been the subject of extensive research in recent years. Among these, the role of metabolic enzymes such as FASN and LDH has been studied less than others. Therefore, the present study was designed to investigate the role of FASN and LDH in bladder cancer patients. One hundred cases diagnosed with bladder cancer and 50 sex-age- matched healthy individuals as control were examined. FASN and LDH serum levels in both patients and controls were determined by human-specific sandwich ELISA kits. Serum levels of FASN and LDH elevated in bladder cancer patients in comparison to healthy individuals (P= 0.03, P= 0.01, respectively). We also found that than higher stages of bladder cancer (III-IV) had higher serum levels of LDH and FASN compared to early stages (I-II) (P= 0.007 and P= 0.006, respectively). Moreover, there was a statistically significant association between smoking history and serum FASN levels in bladder cancer patients (P=0.015). However, there were no remarkable associations between the serum levels of LDH and FASN with other clinicopathological features including sex, age, tumor grade, and tumor size. The data indicate that LDH and FASN may be good and useful biomarkers in the diagnosis and clinical management of bladder cancer. However, further studies are needed.